Surgical pupil reconstruction for congenital idiopathic acorea with lens transparency saving. Case report - Боброва, Надія Федорівна; Романова, Тетяна Вікторівна; Довгань, Ольга Димитріївна (My University, 2025)
Introduction Idiopathic congenital acorea is extremely rare. There are several techniques for preserving the clear lens during pupil formation. Case presentation The complete pupil absence caused acute glaucoma attack 2 weeks after birth, which was controlled in a 1-month-old child by peripheral iridectomy and disconnecting iris-corneal synechias. Six years later pupilloplasty was performed. Under the iris was found a dense white membrane tightly fused with the iris but separated from the lens anterior capsule during preliminary blind viscodissection. Introducing viscoelastic into the pinhole allowed forming a round pupil 3.0 mm in diameter with vitreal scissors and vitrectomy and maintain the anterior capsule intactness and lens transparency. The artificial pupil exhibited a good cosmetic effect. Low visual acuity (1.7 logMAR) can be explained by a long deprivation period, resulted in deep amblyopia and axial myopia. Сlinical discussion Previously, artificial pupil formation have been performed with partial, not complete, pupil absence because the eyes had an anterior chamber. Fluid and IOP levels remained within normal limits as the flow between the chambers occurred. This is confirmed by detecting slit-shaped pupils hidden in the iris folds using mydriatics. The presence of pinpoint or slit-shaped pupils allowed light to enter the eyes and residual form vision. Conclusion Congenital acorea causes acute glaucoma attack due to a lack of fluid outflow between the anterior and posterior chambers. The differential diagnosis between microcoria and acorea is clinically challenging. Preserving lens transparency in pupilloplasty for acorea was possible by gentle viscodesection technique and vitreal instruments.
Keywords: акорія; Acorea; Iridectomy; Pupilloplasty; Angle-closure glaucoma